VANADIUM COMPOUNDS – NEW POTENTIAL DIABETES DRUGS - Dinčić, Marko; Colovic, Mirjana B.; Todorovic, Jasna (Medicinski podmladak, 2023)
The general goals of diabetes treatment are to maintain optimal individualized glycemic targets and to prevent complications. Today, there are significant barriers to successful diabetes therapy, such as parenteral drug administration, decreased therapeutic efficacy after an initial improvement in glycemia, inaccessibility of new medicines in lower-income countries, and high drug prices. Accordingly, significant research attention has been devoted to the development of a cheap and comfortable antidiabetic agent, which demonstrates success in lowering blood glucose levels as well as fewer toxicity properties. In recent years, the effects of inorganic and organic vanadium compounds have been investigated in diabetes treatment. These studies have found the low bioavailability of orally administered inorganic vanadium salts; thus, effective doses to reduce blood glucose levels to normal may cause serious adverse events. In addition, the only study with an organo-vanadium compound (bis(maltolato)oxovanadium(IV)), which has reached Phase IIa clinical trial, was terminated after three months because of renal complications. Moreover, despite a growing interest in polyoxovanadates for treating diabetes in the last few years, the toxic potentials of these compounds are still unknown. However, the precise mechanism of their antidiabetic actions remains unclear. A broad spectrum of possible mechanisms and hypotheses, such as enhancement of insulin secretion and enhanced sensitivity to insulin as well as suppression of hepatic glucose production and decrease of intestinal glucose absorption, have been presented. In conclusion, besides the promising results obtained in animal and human studies, no vanadium compound has successfully reduced blood glucose with acceptable safety and tolerability. More studies of vanadium benefit-risk could lead to a new era in vanadium biomedicine.
Keywords: diabetes; diabetes treatment; vanadium; Inorganic and organic vanadium compounds; polyoxovanadate